Maturity of health care testbeds – A qualitative mapping at the Nordic context - Kielo-Viljamaa Emilia; Collanus Eva; Lahtiranta Janne; Tuomisto Antti (Finnish Social and Health Informatics Association, 2022)
This qualitative mapping aimed to report health care testbed activities in Finland and two other Nordic countries and describe the maturity of these testbeds. The data were collected in 2021 with semi-structured interviews from twelve organizations, of which seven were university hospitals, four universities of applied sciences and one primary health care organization. The data were analyzed using deductive content analysis based on previously identified maturity factors: resources, facilities, marketing and communications, repeatability, contract models, certification and standards compliance and time at the market area. According to the results, there were testbed activities in all participating organizations. The testbed activities mainly were funded from various projects, and the staff mainly consisted of single employees. The testbed facilities were both real-life environments and test or simulation labs. The marketing and communications were based on web pages, social media, events and networks. The repeatability was ensured primarily with usability testing, and the contract models were under development in most organizations. Certification and standards of compliance were rare. Time at the market area was relatively short in many organizations as the activities were mainly testing single products or services rather than continuous co-creation. Testbed activities in the health care and higher education organizations are merging with the daily operations in Nordic countries. Specialization within the organizations was seen, for example, robotics, rehabilitation or medical devices. Testbed organizations highlighted the need for more structured and coordinated processes and activities in order to ensure the management, quality and effectiveness of their testbed services.